Linux "versus" windows - Da Costa Carballo, Carlos M. (Revista General de Información y Documentación, 2002)
This article aims to show the advantages of the Linux operating system compared with Windows. Among these, the most important but by no means the only advantages of Linux are its stability and price - Linux is free of charge.